Exploring privatisation as a panacea to the creation of value in South Africa's passenger rail service - Lata, Johanna (Department of Civil Engineering, 2024)
Passenger rail in South Africa is deemed to be problematic because of its poor service quality, with various sources (e.g. National Household Travel Surveys 2003, 2013 and 2020) pointing to the service getting progressively worse with the passage of time. To reform passenger rail and change its fate, many governments around the world, beginning in the 1980s, implemented different forms of privatisation, mainly partnerships between governments and private companies. This became the face of passenger rail, and it is what some stakeholders are advocating for in South Africa. This dissertation, therefore, used four case studies – namely, the United Kingdom, Argentina, Kenya and South Africa (Gautrain) - as well as in-depth interviews with 9 experts and 2 rail users, to explore whether privatisation is a panacea to an ailing railway, and the value it can bring. Assessment of privatisation in the literature, case studies and expert interviews was done using analysis and comparison across a number of indicators, which have been found to influence the outcomes of privatisation. The findings from the three data sources mostly supported each other, in addition to some very interesting insights uncovered from the interviews. Based on the findings, the dissertation concluded that passenger rail privatisation was not a panacea to improve its poor service quality. However, given the appropriate conditions and processes derived from the matrices used, rail privatisation can result in benefits for the rail user in South Africa. These findings and the recommendations made in the final chapter contribute to the debates and thinking behind passenger rail privatisation in South Africa, and thus help to chart a way forward